Some boundedness properties of solutions to the Vafa–Witten equations on closed 4-manifolds - Tanaka, Y (Oxford University Press, 2017)
We consider a set of gauge-theoretic equations on closed oriented 4-manifolds, which was introduced by Vafa and Witten. The equations involve a triple consisting of a connection and extra fields associated to a principal bundle over a closed oriented 4-manifold. They are similar to Hitchin’s equations over compact Riemann surfaces, and as part of the resemblance, there is no L2-bound on the curvature without an L2-bound on the extra fields. In this article, however, we observe that under the particular circumstance where the curvature does not become concentrated and the limiting connection is not locally reducible, one obtains an L2-bound on the extra fields.